TELEVISION BROADCASTING ENGINEERING NEWS ONLINE THROUGH THE INTERNET BY DYNAMIC WEB - Endro Purwanto; Ir. Fitri Sjafrina, MM (Jurnal Sistem Informasi, 2008)
The development of television so quickly and accompanied by the emergence of thereporters search of reliable news, is a very good composition. With this scientificwriting hopefully be an inspiration for the television world of Indonesia to deliver notonly television news only. The Internet is a medium which can also be used for thedelivery of news using a website. According to observations by the author today,making this website only uses the php programming language and MySQL database.Many people who do not have time to watch television news because the activitiesare intensive. Old news that even need a filing, it aims to facilitate the search fornews returned if needed.In scientific writing, the writer has managed to create a database design that can beconnected to the php programming language. The authors give the name of thedatabase dbkkp and had eleven tables. But not all the tables are the authors discussedhere. The design has become a ready-made applications after repeatedly testing theprogram authors.Television world and the news will not be separated, to deliver information quicklyand clearly was through this medium. But if there are still people who can not watchthe news on television it would be nice to help them communicate using other media.